The road to the Sustainable Development Goals: building global alliances and norms. Issue 2 (4th May 2019) - Gasper, Des
ABSTRACT: Several insider accounts of the formation of the Sustainable Development Goals suggest that the process (the procedures used and the emergent organizational and governance system features) was as important as the resulting goal-set. The paper looks at both aspects, and relationships between them: the rising influence of Southern nations (seen in the roles played by Colombia, Brazil, some African countries and the G77); the partial transcendence of traditional inter-bloc negotiation, including through adoption of elements of deliberative decision-making; the major involvement of civil society and business organizations, thanks especially to the IT revolution; the adoption of a goals-targets-indicators frame that has flexibility at national level and implicit reliance on intensive further civil society activism and monitoring. The paper considers these features and the implied prospects for the SDGs in relation to various perspectives on global governance, with special reference to norm-setting: Ruggie's concepts of 'global public domain' and 'polycentric global governance', Risse and Sikkink's 'norms cascade', Murphy's posited required elements for progressive global innovation, and Raskin's model of transition through responses to crises. It concludes with questions for further work, including regarding the possibly problematic absence of an explicit inspirational value-core.